THE INFLUENCE OF SELF EFFICACY AND KNOWLEDGE SHARING ON TEACHER PROFESSIONALISM THROUGH SITUATIONAL LEADERSHIP - Hamdan, Syahrul (ATTA`DIB, 2025)
Abstract This research aims to determine the influence of self-efficacy, situational leadership, and knowledge sharing on the professionalism of ASN teachers at public elementary schools in Caringin District, Bogor Regency. This research uses a quantitative research approach, which is a process of finding knowledge that uses data in the form of numbers as a tool to find information about what we want to know. This research also uses the path analysis method which is used to analyze the pattern of relationships between variables. The population in this study were all ASN teachers at Caringin District Public Elementary Schools, Bogor Regency, totaling 192 people. The research sample consisted of 131 teachers. The research results show that there is a positive and significant direct influence of Self Efficacy and knowledge sharing on teacher professionalism through situational leadership